Cholesterol Balance in Prion Diseases and Alzheimer’s Disease - Samia Hannaoui; Su Yeon Shim; Yo Ching Cheng; Erica Corda; Sabine Gilch (Viruses, 2014)
Prion diseases are transmissible and fatal neurodegenerative disorders of humans and animals. They are characterized by the accumulation of PrPSc, an aberrantly folded isoform of the cellular prion protein PrPC, in the brains of affected individuals. PrPC is a cell surface glycoprotein attached to the outer leaflet of the plasma membrane by a glycosyl-phosphatidyl-inositol (GPI) anchor. Specifically, it is associated with lipid rafts, membrane microdomains enriched in cholesterol and sphinoglipids. It has been established that inhibition of endogenous cholesterol synthesis disturbs lipid raft association of PrPC and prevents PrPSc accumulation in neuronal cells. Additionally, prion conversion is reduced upon interference with cellular cholesterol uptake, endosomal export, or complexation at the plasma membrane. Altogether, these results demonstrate on the one hand the importance of cholesterol for prion propagation. On the other hand, growing evidence suggests that prion infection modulates neuronal cholesterol metabolism. Similar results were reported in Alzheimer’s disease (AD): whereas amyloid β peptide formation is influenced by cellular cholesterol, levels of cholesterol in the brains of affected individuals increase during the clinical course of the disease. In this review, we summarize commonalities of alterations in cholesterol homeostasis and discuss consequences for neuronal function and therapy of prion diseases and AD.